Avian Influenza Outbreaks in Southeast Asia Affects Prices, Markets and Trade: A Short Case Study - Burgos, Sigfrido; Burgos, Sergio A. (International Journal of Poultry Science, 2007)
Poultry deaths caused by Highly Pathogenic Avian Influenza (HPAI), loss of consumer confidence, government-mandated culling and export bans are some of the reasons for reduced supply of poultry products to food markets. Reluctance to purchase poultry and its products due to fears of disease contraction has increased demand for other sources of animal protein, which in turn raised prices for other meats. HPAI and its effect on poultry meat consumption disrupt poultry trade patterns.